2014
DOI: 10.1111/febs.13015
|View full text |Cite
|
Sign up to set email alerts
|

Novel mode of action of plant defense peptides – hevein‐like antimicrobial peptides from wheat inhibit fungal metalloproteases

Abstract: The multilayered plant immune system relies on rapid recognition of pathogen-associated molecular patterns followed by activation of defenserelated genes, resulting in the reinforcement of plant cell walls and the production of antimicrobial compounds. To suppress plant defense, fungi secrete effectors, including a recently discovered Zn-metalloproteinase from Fusarium verticillioides, named fungalysin Fv-cmp. This proteinase cleaves class IV chitinases, which are plant defense proteins that bind and degrade c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 43 publications
4
59
0
5
Order By: Relevance
“…Consistent with our data, Slavokhotova et al . () showed that the inhibition of a F. verticillioides fungalysin by a hevein‐like peptide from wheat results in the inhibition of hyphal elongation, indicating that fungalysin plays a role in fungal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our data, Slavokhotova et al . () showed that the inhibition of a F. verticillioides fungalysin by a hevein‐like peptide from wheat results in the inhibition of hyphal elongation, indicating that fungalysin plays a role in fungal development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sanz-Martin et al (2016) showed that a fungalysin metalloprotease gene (Cgfl) in Colletotrichum graminicola is also involved in fungal virulence on maize, suggesting that chitinase-cleavage activity of fungalysin is required for full virulence. Moreover, it has been shown that inhibition of fungalysin in Fusarium verticillioides by using a wheat hevein-like peptide also inhibits the hyphal elongation, indicating that fungalysin plays a role in fungal development as well (Slavokhotova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The hevein-like AMPs discovered so far in plants were shown to possess antifungal activity in in vitro assays [32,38,39,[46][47][48][49][50][51][52][53][54]. Binding to chitin and related carbohydrates is supposed to be important for antifungal activity of chitin-binding proteins [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of these peptides was established and consists of the specific inhibition of a metal dependent protein ase of fungi Fusarium Link. A model has been devel oped, according to which, the protective effect of these peptides is due to the inhibition of fungal pro tease, which prevents inactivation of protective the plant chitinases that hydrolyze chitin cell walls of fungi and, thus, inhibit their growth [131].…”
Section: Immunity and Ecological Plasticitymentioning
confidence: 99%